Maternal risk factors and adverse birth outcomes associated with HELLP syndrome: a population‐based study. (13th April 2020) - Lisonkova, S; Razaz, N; Sabr, Y; Muraca, GM; Boutin, A; Mayer, C; Joseph, KS; Kramer, MS
Abstract : Objectives: We assessed the incidence, risk factors and adverse birth outcomes associated with elevated liver enzymes and low platelets (HELLP) syndrome. Design: A retrospective population‐based cohort study. Setting: Canada (excluding Quebec), 2012/2013–2015/2016. Population: Mothers with a singleton hospital live birth or stillbirth at ≥24 weeks' gestation ( n  = 1 078 323). Methods: HELLP syndrome was identified using ICD‐10‐CA diagnostic code from delivery hospitalisation data. We used logistic regression to identify independent risk factors for HELLP syndrome by obtaining adjusted odds ratios (AOR) and 95% confidence intervals (CI), and to assess the associations with adverse outcomes. Main outcome measures: Adverse maternal (e.g. eclampsia) and fetal/neonatal outcomes (e.g. intraventricular haemorrhage, perinatal death). Results: The incidence of HELLP syndrome was 2.5 per 1000 singleton deliveries ( n  = 2663). Risk factors included: age ≥35 years, rural residence, nulliparity, parity ≥4, pre‐pregnancy and gestational hypertension and diabetes, assisted reproduction, chronic cardiac conditions, systemic lupus erythematosus, obesity, chronic hepatic conditions, placental disorders (e.g. fetomaternal transfusion) and congenital anomalies. PROM and age <25 years were inversely associated with HELLP syndrome ( P ‐values <0.05). Women with the syndrome had a 10‐fold higher maternal mortality (95% CI 1.6–84.3) and elevated severe maternal morbidity (9.6 versus 121.7 per 1000; AOR 12.5, 95% CI 11.1–14.1); and higher perinatal mortality (4.3 versus 21.0 per 1000; AOR 4.5, 95% CI 3.5–5.9) and perinatal mortality/severe neonatal morbidity (21.2 versus 202.4 per 1000; AOR 10.7, 95% CI 9.7–11.8). Conclusion: HELLP syndrome is associated with specific pre‐pregnancy and pregnancy risk factors, higher rates of maternal death, and substantially higher severe maternal morbidity, perinatal mortality and severe neonatal morbidity. Tweetable abstract: HELLP syndrome is associated with higher maternal death rate, and substantially higher severe maternal and neonatal morbidity, and perinatal mortality. Tweetable abstract: HELLP syndrome is associated with higher maternal death rate, and substantially higher severe maternal and neonatal morbidity, and perinatal mortality.